2020
DOI: 10.1093/neuonc/noaa029
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular vesicles and PD-L1 in glioblastoma-mediated immunosuppressive monocyte induction

Abstract: Abstract Background Immunosuppression in glioblastoma (GBM) is an obstacle to effective immunotherapy. GBM-derived immunosuppressive monocytes are central to this. Programmed cell death ligand 1 (PD-L1) is an immune checkpoint molecule, expressed by GBM cells and GBM extracellular vesicles (EVs). We sought to determine the role of EV-associated PD-L1 in the formation of immunosuppressive mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…This contributes to the pre‐metastatic niche, paving the way for subsequent metastases. PD‐L1 expression by tumour‐derived EVs can inhibit CD8 T‐cell proliferation, cytokine production and cytotoxicity, 41 and in turn induce the proliferation of other immunosuppressive cell types, such as PD‐1 positive nonclassical monocytes (NCM) 42 …”
Section: Introductionmentioning
confidence: 99%
“…This contributes to the pre‐metastatic niche, paving the way for subsequent metastases. PD‐L1 expression by tumour‐derived EVs can inhibit CD8 T‐cell proliferation, cytokine production and cytotoxicity, 41 and in turn induce the proliferation of other immunosuppressive cell types, such as PD‐1 positive nonclassical monocytes (NCM) 42 …”
Section: Introductionmentioning
confidence: 99%
“…LGG is the main subtype of gliomas, which characterized with lower aggressiveness and well differentiation than GBM counterpart. A growing number of studies focus on the interplay between glioma and immunity, but most research attach great attentions to the GBM [24][25][26]. LGG seems to be ignored from the field of cancer immunotherapy due to its better prognosis than GBM.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was correlated to the increased amount of EVassociated miR-10a and miR-21 that was able to activate MDSCs functions by targeting RAR-related orphan receptor alpha (RORA) and PTEN [30]. Further, the same group identified also TEV-associated miR-29a and miR-92a as responsible for MDSCs increased proliferation, but only miR-92a as the mediator of immunosuppressive functions [31].Further, data published in a very recent study, show that MDSCs, induced by glioblastoma-EVs, inhibit T cell proliferation [32].…”
Section: Tevs and Myeloid-derived Suppressor Cellsmentioning
confidence: 93%
“…Interestingly, glioblastoma-derived EVs drive the formation of non-classical monocytes (NCMs), CD14+/PD-1+/CD16+/HLA-DR high [32], a specific immunosuppressive cell population widely described as anti-inflammatory [133,134]. In the same study, the authors reported that TEV-conditioned NCMs inhibit T cell proliferation and that the presence of PD-L1 in TEVs is responsible for this effect [32].…”
Section: Tevs As the Carriers Of Pd-l1mentioning
confidence: 97%